2017
DOI: 10.1007/s13201-017-0586-5
|View full text |Cite
|
Sign up to set email alerts
|

Statistical distribution of rainfall in Uttarakhand, India

Abstract: Understanding of rainfall is an important issue for Uttarakhand, India which having varied topography and due to that extreme rainfall causes quick runoff which warns structural and functional safety of large structures and other natural resources. In this study, an attempt has been made to determine the best-fit distribution of the annual series of rainfall data for the period of 1991-2002 of 13 districts of Uttarakhand. A best-fit distribution such as Chi-squared, Chi-squared (2P), exponential, exponential (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…They concluded that the gamma distribution provided a better result for the hourly rainfall data. On the other hand, Kumar et al [2] conducted in Uttarakhand, India showed different results. The best-fit distribution is applied, with the comparison performed based on the goodness-of-fit test.…”
Section: Introductionmentioning
confidence: 95%
“…They concluded that the gamma distribution provided a better result for the hourly rainfall data. On the other hand, Kumar et al [2] conducted in Uttarakhand, India showed different results. The best-fit distribution is applied, with the comparison performed based on the goodness-of-fit test.…”
Section: Introductionmentioning
confidence: 95%
“…To this end, they fitted seven distribution families (normal, two‐ and three‐parameter log‐normal, two‐ and three‐parameter gamma, Weibull and log‐Pearson Type III) to rainfall time series and the performance of these distributions was compared by a chi‐squared (χ 2 ) test. It was observed that although the selected distributions varied from month to month, annual rainfall was well fitted by the normal distribution (see also Mohamed and Samir ; and Kumar and Shanu ).…”
Section: Introductionmentioning
confidence: 96%
“…Rainfall was a basic fundamental input into most hydrologic processes specifically in the case of runoff generated sediments (Kumar 2017). Because rain is a naturally occurring phenomenon, which makes it a randomly occurring event, or an unpredictable phenomenon regarding its parameters such as intensity uniformity, duration, and drop size.…”
Section: Introductionmentioning
confidence: 99%